"Bio"‐Macromolecules: Polymer‐Protein Conjugates as Emerging Scaffolds for Therapeutics. Issue 1 (9th December 2013) - Borchmann, Dorothee E.; Carberry, Tom P.; Weck, Marcus
<x xml:space="preserve">Abstract</x> Polymer‐protein conjugates are biohybrid macromolecules derived from covalently connecting synthetic polymers with polypeptides. The resulting materials combine the properties of both worlds: chemists can engineer polymers to stabilize proteins, to add functionality, or to enhance activity; whereas biochemists can exploit the specificity and complexity that Nature has bestowed upon its macromolecules. This has led to a wealth of applications, particularly within the realm of biomedicine. Polymer‐protein conjugation has expanded to include scaffolds for drug delivery, tissue engineering, and microbial inhibitors. This feature article reflects upon recent developments in the field and discusses the applications of these hybrids from a biomaterials standpoint. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>